Advancing food safety through aptamer-based electrochemical detection of zearalenone, a potent mycotoxin in grain corn feed - Sukor, Rashidah; Wan Anuar, Wan Nur Afiqah; Mohsin, Aliah Zannierah; Abdullah, Jaafar (2024)
A highly selective and sensitive electrochemical aptasensor will be developed for real-time monitoring of zearalenone (ZEA), a toxic secondary metabolite produced by Fusarium fungi in grain corn feed. Modification of screen-printed carbon electrode with MWCNT and gold nanoparticles and further fabrication with a truncated ZEA aptamer as the biorecognition element. The electrochemical property will be examined with differential pulse voltammetry to observe the change in electron transfer using ferro/ferricyanide system as redox probe. The signals obtained will further be applied to programme a portable sensor device for quantification of zearalenone in real samples. Studies have demonstrated that aptamer-based electrochemical sensors can achieve detection limits in the nanomolar range, making them highly suitable for detecting trace amounts of ZEA in complex food matrices. This research is expected to further optimize electrochemical aptasensors for ZEA detection, potentially providing a cost-effective, portable solution for real-time food safety monitoring.